2011
DOI: 10.1074/jbc.m110.212225
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae Infection of Host Epithelial Cells via Polymeric Immunoglobulin Receptor Transiently Induces Calcium Release from Intracellular Stores

Abstract: The pneumococcal surface protein C (PspC) is a major adhesin of Streptococcus pneumoniae (pneumococci) that interacts in a human-specific manner with the ectodomain of the human polymeric immunoglobulin receptor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 46 publications
6
31
0
Order By: Relevance
“…Remarkably, pneumococci were also able to persist in lysosomes up to 4 h after internalization (Fig. S1), an observation that is in agreement to our previous results (Asmat et al, 2011). Although pneumococci may persist for longer periods in lysosomes and are able to exit phagosomes (Noske et al, 2009), which consequently leads to transcytosis (Ring et al, 1998), the majority of intracellular pneumococci are most likely killed when the pIgR route is exploited.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Remarkably, pneumococci were also able to persist in lysosomes up to 4 h after internalization (Fig. S1), an observation that is in agreement to our previous results (Asmat et al, 2011). Although pneumococci may persist for longer periods in lysosomes and are able to exit phagosomes (Noske et al, 2009), which consequently leads to transcytosis (Ring et al, 1998), the majority of intracellular pneumococci are most likely killed when the pIgR route is exploited.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, wild-type lactococci were not internalized and hence, did not co-localize with Lamp1 ( Fig. 1), which is in agreement to our previous studies (Asmat et al, 2011;Asmat et al, 2012). These results demonstrated that the PspC-pIgR interaction is a key route for pneumococcal endocytosis by epithelial cells and suggested the intracellular trafficking of pneumococci from early endosomes to late endosomal compartments or phagolysosomes.…”
Section: Endocytosis Of Pneumococci Via the Polymeric Igr Into Membrasupporting
confidence: 90%
See 3 more Smart Citations